Spontaneous vesicoureteral reflux resolution in children: A ten-year single-centre experience - Peer Wildbrett; Mandy Schwebs; Jürgen Abel; Holger Lode; Winfried Barthlen (Wolters Kluwer Medknow Publications, 2013)
Background/Aim: To evaluate the spontaneous resolution rate in infants and young children with vesicoureteral reflux (VUR). Patients and Methods: Paediatric patients with VUR treated in our hospital from January 2000 to December 2010 were retrospectively analyzed. Only patients with pretreatment and follow-up voiding cystourethrogram were included into the study. Treatment success was defined as complete VUR resolution. Results: The resolution rate for infants less than 1 year of age was 38.6% (17 of 44 renal units). Renal units with mild-moderate VUR (I-III) had a resolution rate of 40% (12 of 30 renal units) compared to 35.7% (5 of 14 renal units) with severe grade (IV-V) VUR. The resolution rate for children over 1 year of age was 39,1% (9 of 23 renal units). Renal units with mild-moderate VUR (I-III) had a resolution rate of 42.9% (9 of 21 renal units) compared to 0% (0 of 2 renal units) with severe grade (IV-V) VUR. Conclusion: Infants less than 1 year of age with nonsymptomatic, mild, moderate or severe VUR have a spontaneous resolution rate of more than 35% and therefore should receive a primary conservative therapy. Children over 1 year of age with nonsymptomatic mild-moderate VUR (I-III) have a spontaneous resolution rate of about 40% and should receive primary conservative treatment as well.